2007
DOI: 10.1007/s10620-007-9957-3
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidin Prevents Clostridium difficile Toxin-A-Induced Ileal Enteritis in Mice

Abstract: Recent reports suggest increased incidence and severity of Clostridium difficile-associated diseases. These facts have raised the need for additional clarification of pathogenesis and for a search for new therapeutic strategies. This study evaluated the effects of the polysaccharide fucoidin, an L-selectin blocker, on toxin-A-induced mouse enteritis. Fucoidin (25 mg/kg) or saline (0.1 ml) were injected systemically (ocular plexus) 5 min prior to local challenge with toxin A (5 microg/ileal loop) or phosphate-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…We now show that in the presence of EHNA, the effects of ATL313 are much weaker than when the agonist is used alone, which indicates that most of the anti-inflammatory effects of EHNA observed in our model rely on its ability to enhance the concentration of adenosine in the ileal tissue that maximally stimulates A2A receptors. The abundant presence of neutrophils within TxA-induced pseudomembranes is well known (9,34), as is their important role in the pathogenesis of ileal damage induced by C. difficile TxA (2,27). Here, we showed that EHNA reduced TxA-induced MPO activity, suggesting a potent effect of EHNA to inhibit neutrophil infiltration into ileal tissue.…”
Section: Discussionmentioning
confidence: 56%
“…We now show that in the presence of EHNA, the effects of ATL313 are much weaker than when the agonist is used alone, which indicates that most of the anti-inflammatory effects of EHNA observed in our model rely on its ability to enhance the concentration of adenosine in the ileal tissue that maximally stimulates A2A receptors. The abundant presence of neutrophils within TxA-induced pseudomembranes is well known (9,34), as is their important role in the pathogenesis of ileal damage induced by C. difficile TxA (2,27). Here, we showed that EHNA reduced TxA-induced MPO activity, suggesting a potent effect of EHNA to inhibit neutrophil infiltration into ileal tissue.…”
Section: Discussionmentioning
confidence: 56%
“…Samples were evaluated for the severity of epithelial damage, edema, neutrophil infiltration, and hemorrhage, using a scale ranging from 0 (absence of alterations) to 3 (severe) [34].…”
Section: Histopathologic Assessment Of Tissue Sectionsmentioning
confidence: 99%
“…Natural products have been increasingly exploited as a source of therapeutic compounds for a variety of diseases, and interest has recently focused on the properties of sulfated fucans. 13,14 However, as yet, no studies concerning the potential effects of fucoidan in acute pancreatitis have been published. 10,11 Fucoidan has been shown to act as a ligand for either L-or P-selectin, thereby inhibiting leukocyte rolling.…”
mentioning
confidence: 99%